Fabrication of analog signal interface system into digital data for fluxgate sensor vibration - Devi Sidiq (Department of Physics – Universitas Negeri Padang UNP, 2014)
The purpose of this research is to develop an interface communication between vibration measuring device that has analog signals (voltage) with a personal computer, and process its received data to become digital signals data that can be presented. The USB based communication with low speed (1,5 Mbit/s) and full speed (12 Mbit/s) were used interface communication. This research is categorized as laboratory experimental research. Measuring and colleting data were directly collected from vibration measuring device. The maximum sensitivity resolution of the vibration measuring device due to amplitude is 2.19 x 10-3 cm. The processing of received data to become digital signals used MPLAB X IDE for microcontroller program and C# program for creating window application. Digital data layout from the same vibration with different distance of source already showed different input source